The “Return of the Repressed”: The Role of Sexuality in the Reception of Psychoanalysis in Chilean Medical Circles, 1910-1940 [el “Retorno de Lo Reprimido”: El Papel de la Sexualidad en la Recepción del Psicoanálisis en el Círculo Médico Chileno, 1910-1940] - Ruperthuz-Honorato, L (Fundacao Oswaldo Cruz, 2015)
This article discusses the reception of psychoanalysis in Chilean medical circles from the decade of 1910 onwards. The findings make it possible to reconstruct how Freudianism was initially rejected by the incipient local psychiatric milieu, accusing it of being pansexualist. In the 1930s, this situation changed, and a reassessment of psychoanalysis was made at a local level, describing it precisely as a branch of knowledge specialized in sexuality. The highlighting of the “sublimation” mechanism, esteemed for its ability to transmute the danger of the “id” into culturally accepted products, is a milestone that marked this “return of the repressed” of the sexual factor of psychoanalysis in Chile. The possible social, political and economic variables that influenced this phenomenon are duly discussed. © 2015, Fundacao Oswaldo Cruz. All rights reserved.